Preschoolers Benefit Equally From Video Chat, Pseudo-Contingent Video, and Live Book Reading: Implications for Storytime During the Coronavirus Pandemic and Beyond - Gaudreau, Caroline; King, Yemimah A.; Dore, Rebecca A.; Puttre, Hannah; Nichols, Deborah; Hirsh-Pasek, Kathy; Golinkoff, Roberta Michnick (Frontiers in Psychology, 2020)
During the unprecedented COVID-19 crisis, virtual education activities have become more prevalent than ever. One activity that many families have incorporated into their routines while at home is virtual storytime, with teachers, grandparents, and other remote adults reading books to children over video chat. The current study asks how dialogic reading over video chat compares to more traditional forms of book reading in promoting story comprehension and vocabulary learning. Fifty-eight four-year-olds (M age= 52.7, SD = 4.04, 31 girls) were randomly assigned to one of three conditions (Video chat, Live, and Prerecorded). Across conditions, children were read the same narrative storybook by a female experimenter who used the same ten scripted dialogic reading prompts during book reading. In the Video chat (n = 21) and Live conditions (n = 18), the experimenter gave the scripted prompts and interacted naturally and contingently, responding in a timely, relevant manner to children’s behaviors. In the Prerecorded condition (n = 19), children viewed a video of an experimenter reading the book. The Prerecorded condition was pseudo-contingent; the reader posed questions and paused for a set period of time as if to wait for a child’s response. After reading, children completed measures of vocabulary and comprehension. Results revealed no differences in outcome measures between conditions across six different outcome measures, suggesting children comprehended and learned from the story similarly across book formats. Further, children in the three experimental conditions scored significantly higher on measures than children in a fourth condition (control) who had never read the book, confirming that children learned from the three different book formats. However, children were more responsive to the prompts in the Live and Video chat conditions than the Prerecorded condition, suggesting that children recognized that these interactions were contingent with their responses, a feature that was lacking in the Prerecorded condition. Results indicate that children can comprehend books over video chat, suggesting that this technology is a viable option for reading to children, especially during the current pandemic.